Tolerancia del cultivo de maíz (Zea mayz L.) a diferentes condiciones de inundación en su fase de crecimiento para la determinación del tiempo de drenaje en la zona de Babahoyo - Solórzano Galarza, Darwin Estiven (2016)
VIII. SUMMARY. This research was held in the grounds of the farm "San Pablo" of the Technical University of Babahoyo, located at Km 7.5 of the road Babahoyo - Montalvo Los Rios Province, the objective was to evaluate the tolerance of maize to different flood conditions in their growth phase for determining the drainage time. Hybrid corn was used for research S - 810; The variables evaluated were: volume asphyxiated roots, days to male flowering, days to silking, shelf height cob, plant height, diameter and ear length, ear percentage with rot, number of plants and cobs, percentage of lodging, grain yield and percentage of asphyxiated plants. The experimental design was field: randomized complete blocks, consisting of seven treatments and three repetitions. The treatments were the days of flooding by which time tolerance is established; for evaluation of mean Tukey 95% confidence was used. The results showed that the grain yield of hybrid corn S - 810 was affected by the application of a sheet of water during the time of 72 hours to obtain 6.03 t/ha compared with the control, which produced 8 8 t/ha. Applications water sheets: 12, 24, 36, 48 and 60 hours also exerted influence on the agronomic performance of the maize crop.